How to resolve conflict management development - Sheftel, Phoebe A. (ASTD, 2001)
Conflict within an organization can quickly destroy the productivity of both individuals and work teams. This Infoline will show you how to apply the sound principles of conflict resolution to most situations. The issue details two schools of thought on conflict management--the settlement-driven approach and the relationship focused approach-- and allows you to follow a step-by-step approach to implement the best method that will resolve your workplace disagreements.
Includes bibliographical references. - Print version record
Keywords: Conflict management; Gestion des conflits